Nationality, Locality, and Religiosity: Works and Thoughts of Maria Theresia Geme of the Forum for Religious Harmony of East Nusa Tenggara - Rohmawati, Wiwin Siti Aminah; Cholil, Suhadi; Udasmoro, Wening (UIN Sunan Gunung Djati Bandung, 2022)
This article examines Maria Theresia Geme's thoughts and works on the issue of religious harmony through Forum for Religious Harmony (FKUB) of East Nusa Tenggara (NTT). This is a qualitative study which gathers data through observation, in-depth interviews, and document analysis. This research aims to address three primary questions: (1) How the agency of